Clinical development of 1% azithromycin in DuraSite(®), a topical azalide anti-infective for ocular surface therapy - Friedlaender, Mitchell H (Dove Medical Press, 2007)
Conjunctivitis, or inflammation of the conjunctiva, refers to a diverse group of ocular surface diseases of viral or bacterial origin that primarily affect the conjunctiva. In developed countries, the most common causative bacterial pathogens are Staphylococcus aureus, Haemophilus influenzae, and Streptococcus pneumoniae. Most varieties of conjunctivitis are self-limiting; however, some cases can be extremely contagious or cause serious complications if left unchecked. New ocular antibiotics are needed to keep pace with the increasing incidence of bacterial resistance and provide options that decrease the overall treatment burden and encourage patient compliance. Azithromycin is a well known systemic anti-infective with broad spectrum activity against gram positive-, gram negative-, and atypical bacteria species. Ocular use has been limited because its solubility and stability profiles in aqueous media were not favorable for delivery to the eye. An eyedrop of 1% azithromycin in DuraSite(®) (AzaSite™, InSite Vision, Alameda, CA, USA), a bioadhesive ocular drug delivery system, was recently developed and evaluated in clinical trials. This formulation is well tolerated, delivers a high concentration of azithromycin to the conjunctiva, has a broader eradication profile than aqueous azithromycin, and can be effectively dosed with 7 drops, a 65% reduction in the amount of drops required by the most popular antibiotics currently used for conjunctivitis.